PEMBELAJARAN DARING MASA PANDEMI DI JURUSAN SOSIOLOGI UNIVERSITAS RIAU - Sabri Rahmatdi; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The formulation of the problem of this research is how the perception of Sociology FISIP students at Riau University towards online lectures and also how much influence the perceptions of Sociology FISIP students at Riau University towards online lectures. the effect of perceptions of Sociology students, Faculty of Social and Political Sciences, University of Riau on online lectures. The collected data will be coded after the data will be tabulated. Data in tabular format is analyzed and described both quantitatively and descriptively. Based on the results of this study, it can be concluded that most research respondents do not agree with the bold learning method and want to immediately return to learning as usual on campus. The online learning method is considered less effective for the learning system because the research respondent students assess the direct learning system to be much more effective than online lectures. This should be an evaluation so that bold learning can be done innovatively so that it can be well received by students without reducing its essence. and  the need to manage communication  between lectures and students for application in learning disciplineKeywords: Online Lecture, Impact of Online Lecture, Student Perception of Online Lecture